KRITIK TRADISI ILMIAH BARAT: MENYOROT FUNGSIONALITAS METODE ILMIAH DALAM PEMBANGUNAN MANUSIA SEUTUHNYA - Syarif, Fajar (FIKRAH, 2017)
This research discusses the development of Western Science, which utters a negative impact in the shaping of society and men as human. The prime factor is the understanding of "Free Value" which is known as the Science of Free Value Morality. The result of the development of this science can not be controlled, which impact to crisis of morality, this research proves that reform and development of scientific traditions must begun from cleaning up epistemology and science must be known culturally.